Individual Investor Risk Tolerance from a Behavioural Finance Perspective in Gauteng, South Africa - van den Bergh-Lindeque, Anzel; Ferreira-Schenk, Sune; Dickason-Koekemoer, Zandri (International Journal of Economics and Financial Issues, 2021)
The investment behaviour of individuals is unconsciously influenced by their thoughts, emotions, personal beliefs or past experiences to the degree that even individual investors with considerable knowledge may diverge from logic and reason. These influences, which can be classified as behavioural finance biases, may affect the manner in which risk is perceived and understood. This study aims to establish the relationship between the behavioural finance biases and the risk tolerance of individual investors within Gauteng, South Africa. This study also aims to identify the behavioural finance biases that drive individual investment decisions. Positive, statistically significant relationships were established between the behavioural finance biases and individual investor risk tolerance. Furthermore, the investment decisions of individual investors are driven to a rather great extent by the behavioural finance biases. The significance of these findings will contribute to facilitate the more practical and accurate profiling of individual investors’ risk tolerance to ensure the successful implementation of investment strategies not only within South Africa, but also internationally. Keywords: individual investors, risk tolerance, risk profiling, behavioural finance, investment decisions, Gauteng, South Africa JEL Classifications: D81, G41 DOI: https://doi.org/10.32479/ijefi.11451